Human Resource Management Concepts: Recruitment, Job Analysis, Job Evaluation, Remuneration and Organizational Development - Candra Susanto, Primadi; Sugiyanto, Sugiyanto; Rachman, Subehana; Hedi Saepudin, Tubagus; Hamonangan Ismail, Dingot (Greenation International Journal of Law and Social Sciences, 2024)
The purpose of this study is expected to be able to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The article on the concept of human resource management: recruitment, job analysis, job evaluation, remuneration, and organizational development is a scientific literature article in the scope of human resource management. The approach or method used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Recruitment plays a role in the Concept of Human Resource Management; 2) Job Analysis plays a role in the Concept of Human Resource Management; 3) Job Evaluation plays a role in the Concept of Human Resource Management; 4) Remuneration plays a role in the Human Resource Management Concept' and 5) Organizational Development plays a role in the Human Resource Management Concept.